Reciclagem química do bagaço de cana-de-açúcar para a produção de membranas assimétricas de diacetato de celulose - Ferreira Júnior, Moacir Fernandes (2009)
In this work, cellulose from sugarcane bagasse was used for producing cellulose acetate aiming the production of asymmetric membranes. The obtained cellulose acetate presented degree of substitution of 2.49, characterized as a cellulose diacetate. Membranes produced from this material were compared to the membrane produced with commercial cellulose acetate (Rhodia). All the produced membranes were asymmetric, characterized by the presence of a dense skin and a porous support. Regarding the morphology, differences on the surface as well as on the porous support are clearly observed. The membrane produced from commercial cellulose diacetate presents a superficial layer (skin) that presents regions with higher density when compared with the membrane produced with cellulose acetate from sugarcane bagasse. Water vapor flux, normalized using the membrane thickness, for the produce membranes were 1.06 10-4 g s-1 cm-2 μm for the membrane produced with Rhodia s cellulose acetate and 1.25 10-4 g s-1 cm-2 μm for cellulose acetate from sugarcane bagasse and 2.00 10-4 g s-1 cm-2 μm for the commercial membrane (Osmonics), utilized in nanofiltration processes and used for comparison in this work. These differences are related to the difference in the viscosity average molecular weigh (vM), which was 46.124 g mol-1 for Rhodia s cellulose acetate and 16.677 g mol-1 for cellulose diacetate from sugarcane bagasse. The differences in water vapor flux was also related to the amount of lignin in cellulose diacetate remaining in cellulose diacetate from sugarcane bagasse.